Preparation method of low-temperature grouting material

By adjusting the ratio of sulfaluminate cement and mineral blends, combined with early strength admixtures, grouting materials suitable for low temperature conditions are prepared, which solves the problem of insufficient strength of grouting materials at low temperatures, and achieves high early strength and The effect of fast hydration.

CN119143459AInactive Publication Date: 2024-12-17INST OF ROCK & SOIL MECHANICS CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411281654.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-03
Filing Date
2024-09-13
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The strength of the existing grouting materials is affected under low temperature conditions, making it difficult to achieve the same effect at room temperature. Especially in tunnel construction in cold plateaus in the western region, it is difficult to meet the early demands of high strength and fast hydration.

Method used

Using a preparation method of low-temperature grouting material, by selecting suitable sulfa aluminate cement types and mineral blends, adjusting the mass fraction of anhydrous calcium sulfa aluminate and gypsum in sulfa aluminate cement, and combining the appropriate amount ordinary silicate cement and early strength admixture, improved basic grouting materials to adapt to low temperature conditions.

Benefits of technology

Under low temperature conditions, the produced low-temperature grouting materials have the advantages of high early strength and fast hydration speed. They can effectively adapt to the low-temperature environment and ensure that their performance is not affected. They are suitable for tunnel construction in cold plateau areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143459A_ABST
    Figure CN119143459A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of grouting materials, in particular to a preparation method of a low-temperature grouting material. The preparation method of the low-temperature grouting material comprises the following steps that 1, the type of sulphoaluminate cement is selected according to the attribute of the needed low-temperature grouting material to prepare the sulphoaluminate cement, and the sulphoaluminate cement is formed by mixing sulphoaluminate clinker with the determined mass fraction and gypsum with the determined type and mass fraction; step 2, selecting a mineral admixture, and adding the mineral admixture into the prepared sulphoaluminate cement to prepare a basic grouting material; 3, testing the first mechanical property and the first physical property of the basic grouting material under the normal temperature condition and the low temperature condition respectively; and whether the low-temperature condition has an inhibiting effect on the basic grouting material or not is judged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grouting materials, and in particular to a preparation method of a low-temperature grouting material. Background Art

[0002] Grouting materials refer to fluid materials that are injected into the gaps and holes of strata, rocks or structures under pressure to increase bearing capacity, prevent leakage and improve the overall performance of the structure. They are mixed with main agent, solvent (water or other solvents) and admixture (curing agent, stabilizer, etc.). In recent years, as the focus of infrastructure construction has gradually shifted to remote areas such as mountainous areas, tunnel projects have accounted for an increasingly large proportion of the lines. In the process of tunnel construction, disasters such as landslides and sudden water inrush emerge in an endless stream. At this stage, measures such as pre-injection of grouting materials to reinforce strata and block water have been widely used.

[0003] At present, most of the existing grouting materials are suitable for normal temperature conditions, but in the cold plateau areas in the west, there are a large number of engineering projects with high altitudes, deep valleys, and long-term low temperatures. Due to the low temperature of the shallow surface layer of the plateau, and the rock joints and fissures are rich in low-temperature water from the melted snow on the top of the mountain and the infiltration of ice lakes at the foot of the mountain, the grouting construction temperature in the tunnel is at a low level, and the low temperature affects the strength development of conventional grouting materials, making it difficult to achieve the same effect at normal temperature.

[0004] Therefore, how to provide a preparation method of a low-temperature grouting material so that the low-temperature grouting material is suitable for low-temperature conditions and still has the characteristics of high early strength and fast hydration rate under low-temperature conditions is a problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] The technical problem to be solved by the present invention is that most of the existing grouting materials in the prior art are suitable for normal temperature conditions, but their strength will be affected under low temperature conditions, making it difficult to achieve the same effect under normal temperature conditions.

[0006] The present invention is implemented by the following technical scheme: A method for preparing a low-temperature grouting material, comprising the following steps: Step 1, selecting the type of sulphoaluminate cement according to the properties of the required low-temperature grouting material to prepare sulphoaluminate cement, wherein the sulphoaluminate cement is mixed with a determined mass fraction of sulphoaluminate clinker and a determined type and mass fraction of gypsum;

[0007] Step 2: Select a mineral admixture and add it to the prepared sulphoaluminate cement to obtain a basic grouting material;

[0008] Step 3, testing the first mechanical property and the first physical property of the basic grouting material under normal temperature and low temperature conditions respectively; judging whether the low temperature condition has an inhibitory effect on the basic grouting material; and:

[0009] If there is no inhibition, the basic grouting material is marked as the low-temperature grouting material to be prepared;

[0010] If there is an inhibitory effect, the low-temperature performance of the basic grouting material is improved so that the low-temperature condition has no inhibitory effect on the basic grouting material, and the improved basic grouting material is marked as the low-temperature grouting material to be prepared.

[0011] Optionally, in step 1, sulphoaluminate cement is selected according to the following principles;

[0012] a. When the property of the low-temperature grouting material is early high strength, the type of sulphoaluminate cement selected is early high strength sulphoaluminate cement;

[0013] b. When the property of the low-temperature grouting material to be prepared is expansion performance, the type of sulphoaluminate cement is selected as expansive sulphoaluminate cement;

[0014] c. When the property of the low-temperature grouting material to be prepared is high self-stress, the type of sulphoaluminate cement selected is self-stress sulphoaluminate cement;

[0015] d. When the property of the low-temperature grouting material to be prepared is low alkalinity, the type of sulphoaluminate cement selected is low-alkalinity sulphoaluminate cement.

[0016] Optionally, step 1 includes the following sub-steps:

[0017] Step 101, setting the mass fraction W3 of anhydrous calcium sulphoaluminate in the sulphoaluminate cement;

[0018] Step 102, determining the mass fraction W1 of the sulphoaluminate clinker according to the mass fraction W3 of the anhydrous calcium sulphoaluminate;

[0019] Step 103: Determine the type of gypsum and the mass fraction W2 of gypsum according to the type of sulphoaluminate cement and the mass fraction W1 of sulphoaluminate clinker.

[0020] Optionally, the mass fraction W3 of the anhydrous calcium sulphoaluminate is 30%-40%, and the water-cement ratio of the sulphoaluminate cement is 0.35-0.5. Optionally, step 102 is performed as follows: according to the formula W1=W3 / W4, wherein W4 is the mass fraction of the anhydrous calcium sulphoaluminate in the sulphoaluminate clinker.

[0021] Optionally, step 103 includes the following steps:

[0022] Step 1031, determining M according to the type of the sulphoaluminate cement, wherein M is the ratio of the mass of sulfur trioxide in the gypsum to the mass of sulfur trioxide required for hydration of anhydrous calcium sulphoaluminate to form ettringite, and the value of M is determined according to the following principles;

[0023] h. When the type of sulphoaluminate cement is early high-strength sulphoaluminate cement, M is 0-1;

[0024] i. When the type of sulphoaluminate cement is expansive sulphoaluminate cement, M is 1-2;

[0025] j. When the type of sulphoaluminate cement is self-stressed sulphoaluminate cement, M is 2-4;

[0026] k. When the type of sulphoaluminate cement is low-alkalinity sulphoaluminate cement, M is 2.5-3.

[0027] Step 1032: Determine the ratio C of the mass fraction W1 of the sulphoaluminate clinker to the mass fraction W2 of the gypsum according to the M. G , the C G Set to: Among them, A C is the mass fraction of anhydrous calcium sulphoaluminate in the sulphoaluminate clinker, which is the same as W4, and S is the mass fraction of sulfur trioxide in the gypsum;

[0028] Step 1033: based on the mass fraction W1 of the sulphoaluminate clinker and the mass fraction ratio C G Determine the mass fraction W2 of the gypsum;

[0029] Step 1034, determining the type of the gypsum according to the type of the sulphoaluminate cement is performed according to the following principles:

[0030] w. When the property of the low-temperature grouting material is early high strength, when the type of the sulphoaluminate cement is early high strength sulphoaluminate cement, the type of the gypsum is dihydrate gypsum or anhydrous gypsum;

[0031] x. When the property of the low-temperature grouting material to be prepared is expansion performance, when the type of the sulphoaluminate cement is expansive sulphoaluminate cement, the type of the gypsum is dihydrate gypsum;

[0032] y. When the property of the low-temperature grouting material to be prepared is high self-stress, when the type of the sulphoaluminate cement is self-stress sulphoaluminate cement, the type of the gypsum is dihydrate gypsum;

[0033] z. When the property of the low-temperature grouting material to be prepared is low alkalinity, when the type of the sulphoaluminate cement is low-alkalinity sulphoaluminate cement, the type of the gypsum is anhydrous gypsum.

[0034] That is, based on principles a / b / c / d, the type of gypsum can also be directly determined based on the properties of the low-temperature grouting material.

[0035] Optionally, before adding the mineral admixture to the prepared sulphoaluminate cement, the following steps are further included:

[0036] 5-15wt% of ordinary Portland cement 32.5, 5-15wt% of ordinary Portland cement 42.5 or 5-15wt% of ordinary Portland cement 52.5 is added to the sulphoaluminate cement.

[0037] Optionally, the step 2 includes:

[0038] Step 201: According to the preparation requirements of the low-temperature grouting material, the type of the mineral admixture is selected, and the type of the mineral admixture includes at least one of the following: slag, fly ash, limestone powder or silica fume; wherein the type of the mineral admixture is selected according to the following principles:

[0039] A. When the preparation requirement is to improve the strength of the low-temperature grouting material, the type of the mineral admixture is selected as slag or fly ash;

[0040] B. When the preparation requirement is to increase the density of the slurry, the type of the mineral admixture is selected to be silica fume or limestone powder;

[0041] C. When the preparation requirement is to reduce the amount of cementitious material, the type of the mineral admixture is selected as slag or silica fume;

[0042] Step 202, determining the optimal amount of the mineral admixture according to the type of the mineral admixture comprises:

[0043] Step 203: Determine the initial addition amount range of the mineral admixture according to the type of the mineral admixture, wherein:

[0044] The initial addition amount of the slag ranges from 20% to 70% of the mass of the sulphoaluminate clinker;

[0045] The initial addition amount of the fly ash ranges from 20% to 40% of the mass of the sulphoaluminate clinker;

[0046] The initial addition amount of the limestone powder is in the range of 0wt%-15wt%, and the initial addition amount of the silica fume is in the range of 5wt%-10wt%.

[0047] Several different addition amounts are selected within the initial addition amount range of the same mineral admixture to set up several groups of comparative tests, and the 1d compressive strength, 1d flexural strength and fluidity of the sulphoaluminate cement before the addition of the mineral admixture and after the addition of the mineral admixture in several groups of comparative tests are tested, and the addition amount of the mineral admixture in the comparative test when the 1d compressive strength, the 1d flexural strength and the fluidity are optimal values ​​is taken as the optimal addition amount.

[0048] Optionally, the first physical property in step 3 includes initial fluidity, fluidity loss over time within one hour, and expansion rate;

[0049] The first mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength and 3d compressive strength;

[0050] The presence of an inhibitory effect means at least one of the following:

[0051] The basic grouting material has a 1d flexural strength under low temperature conditions that is less than 60% of the 1d flexural strength under normal temperature conditions, a 3d flexural strength under low temperature conditions that is less than 60% of the 3d flexural strength under normal temperature conditions, a 1d compressive strength under low temperature conditions that is less than 60% of the 1d compressive strength under normal temperature conditions, a 3d compressive strength under low temperature conditions that is less than 60% of the 3d compressive strength under normal temperature conditions, an initial fluidity under low temperature conditions that is less than 250mm, a fluidity loss over time within one hour under low temperature conditions that exceeds 20%, or a negative expansion rate under low temperature conditions.

[0052] Optionally, the low temperature performance improvement in step 3 includes:

[0053] Step S1, increasing the dosage of at least one of the following types of ordinary Portland cement: ordinary Portland cement 32.5, ordinary Portland cement 42.5 or ordinary Portland cement 52.5;

[0054] or,

[0055] Step S2, adding an early strength admixture to the basic grouting material;

[0056] Step S2 includes adding an early strength admixture to the basic grouting material according to the following steps:

[0057] Step S201, determining the dosage range of the early strength admixture, wherein the early strength admixture includes at least one of the following: sodium sulfate, aluminum sulfate, sodium nitrite, calcium nitrite, calcium nitrate, lithium carbonate, calcium formate, sodium gluconate, triethanolamine, triisopropanolamine, ethylene glycol, urea or sucrose, wherein the dosage range of the sodium sulfate is 0.3-3wt%, the dosage range of the aluminum sulfate is 0-4wt%, the dosage range of the sodium nitrite is 0.3-1wt%, the dosage range of the calcium nitrite is 0.3-1wt%, the dosage range of the nitric acid is 0. The dosage range of calcium is 0.5-5wt%, the dosage range of lithium carbonate is 0-0.1wt%, the dosage range of calcium formate is 0.1-2wt%, the dosage range of sodium gluconate is 0.03-0.07wt%, the dosage range of triethanolamine is 0.05-0.6wt%, the dosage range of triisopropanolamine is 0.2-0.9wt%, the dosage range of ethylene glycol is 3-5wt%, the dosage range of urea is 0-3wt%, and the dosage range of sucrose is greater than 0.2wt%;

[0058] Step S202, determining X preferred early strength admixtures according to the dosage range, wherein X≥1;

[0059] Step S203, determining the optimal dosage of X preferred early strength admixtures;

[0060] Step S204, adding the preferred early strength admixture into the basic grouting material according to the optimal dosage;

[0061] The step S202 of determining X preferred early strength admixtures according to the dosage range includes:

[0062] Step S2021, selecting 1-2 dosage values ​​within the dosage range of each of the early strength admixtures,

[0063] Step S2022: adding different early strength admixtures to the basic grouting material according to the selected dosage values ​​to obtain a plurality of different first sample materials, and testing and comparing the second mechanical properties and the second physical properties of the plurality of first sample materials.

[0064] Step S2023, determining X preferred early strength admixtures according to the second mechanical properties and the second physical properties; the second mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength, 3d compressive strength, cohesion and internal friction angle; the second physical properties include initial fluidity, fluidity loss over time within one hour and expansion rate;

[0065] and:

[0066] When X=1, the determining of the optimal dosage of X preferred early strength admixtures includes: selecting N dosage point values ​​within the dosage range of the preferred early strength admixture, wherein N≥4, the N dosage point values ​​form an arithmetic progression, and the dosage point values ​​include two boundary values ​​of the dosage range; adding the preferred early strength admixtures with different dosage point values ​​to the basic grouting material according to the selected N dosage point values ​​to obtain N different second sample materials, testing and comparing the second mechanical properties and the second physical properties of the N second sample materials, and determining Y preferred dosages according to the second mechanical properties and the second physical properties, wherein Y≥1; when Y=1, the preferred dosage is the optimal dosage; when Y>1, performing X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy experiments on the Y second sample materials obtained under the Y preferred dosages, analyzing and comparing the phase composition and content of the Y second sample materials, and observing the morphology of the hydration products in the second sample materials, and then determining the optimal dosage from the Y preferred dosages;

[0067] Step S2023, when X>1, determining the optimal dosage of the X preferred early-strength admixtures comprises: selecting N dosage point values ​​within the dosage range of each preferred early-strength admixture, wherein N≥4, the N dosage point values ​​form an arithmetic progression, and the dosage point values ​​include two boundary values ​​of the dosage range; designing an orthogonal experiment, adding different early-strength admixtures with different dosage point values ​​to the basic grouting material according to the selected N dosage point values ​​to obtain (N) X Different second sample materials, tested and compared (N) X The second mechanical properties and the second physical properties of the second sample materials are determined, and Y preferred dosage combinations of X preferred early-strength admixtures are determined according to the second mechanical properties and the second physical properties, wherein Y ≥ 1; when Y = 1, the preferred dosage combination is the optimal dosage combination; when Y > 1, X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy experiments are performed on the Y second sample materials obtained under the Y preferred dosage combinations, the phase composition and content of the Y second sample materials are analyzed and compared, and the morphology of the hydration products in the second sample materials is observed, so as to determine the optimal dosage combination from the Y preferred dosage combinations.

[0068] Compared with the prior art, the present invention has the following beneficial effects:

[0069] The present invention proposes a method for preparing a low-temperature grouting material. First, the type of sulphoaluminate cement required is determined according to the properties of the low-temperature grouting material to be prepared, and then the mass fraction W3 of anhydrous calcium sulphoaluminate in the sulphoaluminate cement is set, and then the mass fraction W1 of sulphoaluminate clinker, the mass fraction W2 of the gypsum and the type of the gypsum are determined. The low-temperature grouting material with corresponding property requirements can be prepared according to the obtained proportion. The sulphoaluminate cement belongs to an inorganic gelling material. As the base of the low-temperature grouting material, it has the advantages of fast hydration speed, high early strength and low cost, and can be applied to low temperature conditions. By first determining the type of mineral admixture, then determining the optimal addition amount, and then adding the optimal amount of mineral admixture into the sulphoaluminate cement, the optimal amount of mineral admixture is added to the sulphoaluminate cement. The basic grouting material is obtained by adding the appropriate type of mineral admixture, which can further improve the physical and mechanical properties and low temperature adaptability of sulphoaluminate cement on the original basis; finally, by testing the first mechanical properties and the first physical properties of the basic grouting material under normal temperature conditions and low temperature conditions, it is judged whether the low temperature condition has an inhibitory effect on the basic grouting material, and then it can be known whether the obtained basic grouting material has properties suitable for low temperature materials. If not, it means that the basic grouting material can adapt to the low temperature environment well and can be used directly. If so, the low temperature performance of the basic grouting material is improved, so that the improved basic grouting material can adapt to the low temperature environment, and then it can be ensured that the low temperature grouting material has low temperature adaptability. The performance of the low temperature grouting material obtained by the preparation method of the present invention is not affected by the low temperature conditions, and it still has the advantages of high early strength and fast hydration rate under low temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 The overall process of a method for preparing a low-temperature grouting material proposed in Example 1 of the present invention Figure 1 ;

[0071] Figure 2 The overall process of a method for preparing a low-temperature grouting material proposed in Example 1 of the present invention Figure 2 ;

[0072] Figure 3 This is a flow chart of a method for preparing a low-temperature grouting material proposed in Example 2 of the present invention. DETAILED DESCRIPTION

[0073] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0074] Embodiment 1:

[0075] like Figure 1-2The present invention provides a method for preparing a low-temperature grouting material, comprising the following steps:

[0076] Step 1: Select the type of sulphoaluminate cement according to the properties of the required low-temperature grouting material to prepare sulphoaluminate cement, wherein the sulphoaluminate cement is prepared by mixing a sulphoaluminate clinker having a determined mass fraction and a gypsum having a determined type and mass fraction;

[0077] Step 2: Select a mineral admixture and add it to the prepared sulphoaluminate cement to obtain a basic grouting material;

[0078] Step 3, testing the first mechanical property and the first physical property of the basic grouting material under normal temperature and low temperature conditions respectively; judging whether the low temperature condition has an inhibitory effect on the basic grouting material; and:

[0079] If there is no inhibition, the basic grouting material is marked as the low-temperature grouting material to be prepared;

[0080] If there is an inhibitory effect, the low-temperature performance of the basic grouting material is improved so that the low-temperature condition has no inhibitory effect on the basic grouting material, and the improved basic grouting material is marked as the low-temperature grouting material to be prepared.

[0081] In this scheme, in step 1, sulphoaluminate cement is selected according to the following principles:

[0082] a. When the property of the low-temperature grouting material is early high strength, the type of sulphoaluminate cement selected is early high strength sulphoaluminate cement;

[0083] b. When the property of the low-temperature grouting material to be prepared is expansion performance, the type of sulphoaluminate cement is selected as expansive sulphoaluminate cement;

[0084] c. When the property of the low-temperature grouting material to be prepared is high self-stress, the type of sulphoaluminate cement selected is self-stress sulphoaluminate cement;

[0085] d. When the property of the low-temperature grouting material to be prepared is low alkalinity, the type of sulphoaluminate cement selected is low-alkalinity sulphoaluminate cement.

[0086] Specifically, the step 1 includes the following sub-steps:

[0087] Step 101, setting the mass fraction W3 of anhydrous calcium sulphoaluminate in the sulphoaluminate cement;

[0088] Step 102, determining the mass fraction W1 of the sulphoaluminate clinker according to the mass fraction W3 of the anhydrous calcium sulphoaluminate;

[0089] Step 103: Determine the type of gypsum and the mass fraction W2 of gypsum according to the type of sulphoaluminate cement and the mass fraction W1 of sulphoaluminate clinker.

[0090] It should be noted that the mass fraction W3 of the anhydrous calcium sulphoaluminate is 30%-40%, and the water-cement ratio of the sulphoaluminate cement is 0.35-0.5.

[0091] This is because, according to the properties of the low-temperature grouting material to be prepared, the type of sulphoaluminate cement with corresponding properties is selected, so that when the types of sulphoaluminate cement selected are early high-strength sulphoaluminate cement, expansive sulphoaluminate cement, self-stress sulphoaluminate cement or self-stress sulphoaluminate cement, the prepared low-temperature grouting materials have early high strength, expansibility, high self-stress or low alkalinity respectively, and thus low-temperature grouting materials with different properties can be prepared according to different low-temperature environments, and different material requirements can be met according to local conditions; in sulphoaluminate cement, the content of anhydrous calcium sulphoaluminate and the water-cement ratio are crucial parameters affecting the performance of cement, and a point value is arbitrarily selected in the range of mass fraction of 30%-40% as the mass fraction W3 of anhydrous calcium sulphoaluminate in the sulphoaluminate cement, and the water-cement ratio of the sulphoaluminate cement is 0.35-0.5, so that the obtained sulphoaluminate cement has excellent physical and mechanical properties.

[0092] As an optional implementation method of the present scheme 1, the operation of step 102 is as follows: according to the formula W1=W3 / W4, wherein W4 is the mass fraction of anhydrous calcium sulfoaluminate in the sulfoaluminate clinker.

[0093] More specifically, step 103 includes the following steps:

[0094] Step 1031, determining M according to the type of the sulphoaluminate cement, wherein M is the ratio of the mass of sulfur trioxide in the gypsum to the mass of sulfur trioxide required for hydration of anhydrous calcium sulphoaluminate to form ettringite, and the value of M is determined according to the following principles;

[0095] h. When the type of sulphoaluminate cement is early high-strength sulphoaluminate cement, M is 0-1;

[0096] i. When the type of sulphoaluminate cement is expansive sulphoaluminate cement, M is 1-2;

[0097] j. When the type of sulphoaluminate cement is self-stressed sulphoaluminate cement, M is 2-4;

[0098] k. When the type of sulphoaluminate cement is low-alkalinity sulphoaluminate cement, M is 2.5-3.

[0099] Step 1032: Determine the ratio C of the mass fraction W1 of the sulphoaluminate clinker to the mass fraction W2 of the gypsum according to the M. G , the C G Set to: Among them, A C is the mass fraction of anhydrous calcium sulphoaluminate in the sulphoaluminate clinker, which is the same as W4, and S is the mass fraction of sulfur trioxide in the gypsum;

[0100] Step 1033: based on the mass fraction W1 of the sulphoaluminate clinker and the mass fraction ratio C G Determine the mass fraction W2 of the gypsum;

[0101] Step 1034, determining the type of the gypsum according to the type of the sulphoaluminate cement is performed according to the following principles:

[0102] w. When the property of the low-temperature grouting material is early high strength, when the type of the sulphoaluminate cement is early high strength sulphoaluminate cement, the type of the gypsum is dihydrate gypsum or anhydrous gypsum;

[0103] x. When the property of the low-temperature grouting material to be prepared is expansion performance, when the type of the sulphoaluminate cement is expansive sulphoaluminate cement, the type of the gypsum is dihydrate gypsum;

[0104] y. When the property of the low-temperature grouting material to be prepared is high self-stress, when the type of the sulphoaluminate cement is self-stress sulphoaluminate cement, the type of the gypsum is dihydrate gypsum;

[0105] z. When the property of the low-temperature grouting material to be prepared is low alkalinity, when the type of the sulphoaluminate cement is low-alkalinity sulphoaluminate cement, the type of the gypsum is anhydrous gypsum.

[0106] That is, based on principles a / b / c / d, the type of gypsum can also be directly determined based on the properties of the low-temperature grouting material.

[0107] In the above scheme, this is because the mass fraction W1 of sulphoaluminate clinker can be determined by the formula W1=W3 / W4; then M is determined by the type of sulphoaluminate cement, and then M is substituted into the formula The ratio C of the mass fraction W1 of the sulphoaluminate clinker to the mass fraction W2 of the gypsum can be calculated. G, and then the mass fraction W2 of gypsum is obtained by the mass fraction W1 of the sulphoaluminate clinker obtained above; and then the type of gypsum is determined by the type of sulphoaluminate cement, and then the proportion composition of different types of sulphoaluminate cement can be determined by scientific design according to different types of sulphoaluminate cement, and different types of low-temperature grouting materials can be prepared according to different low-temperature environments to meet different material requirements. In addition, the mass fraction W3 of anhydrous calcium sulphoaluminate in the prepared sulphoaluminate cement can be between 30% and 40%, so that the sulphoaluminate cement has excellent physical and mechanical properties.

[0108] Optionally, before adding the mineral admixture to the prepared sulphoaluminate cement, the following steps are further included:

[0109] 5-15wt% of ordinary Portland cement 32.5, 5-15wt% of ordinary Portland cement 42.5 or 5-15wt% of ordinary Portland cement 52.5 is added to the sulphoaluminate cement.

[0110] Those skilled in the art will appreciate that by adding 5-15wt% of ordinary Portland cement 32.5, 5-15wt% of ordinary Portland cement 42.5 or 5-15wt% of ordinary Portland cement 52.5 to the sulphoaluminate cement, the sulphoaluminate cement and ordinary Portland cement can be mixed to promote hydration, thereby increasing the degree of reaction of the composite cement material at low temperatures.

[0111] Optionally, the step 2 includes:

[0112] Step 201: According to the preparation requirements of the low-temperature grouting material, the type of the mineral admixture is selected, and the type of the mineral admixture includes at least one of the following: slag, fly ash, limestone powder or silica fume; wherein the type of the mineral admixture is selected according to the following principles:

[0113] A. When the preparation requirement is to improve the strength of the low-temperature grouting material, the type of the mineral admixture is selected as slag or fly ash;

[0114] B. When the preparation requirement is to increase the density of the slurry, the type of the mineral admixture is selected to be silica fume or limestone powder;

[0115] C. When the preparation requirement is to reduce the amount of cementitious material, the type of the mineral admixture is selected as slag or silica fume;

[0116] Step 202, determining the optimal amount of the mineral admixture according to the type of the mineral admixture comprises:

[0117] Step 203: Determine the initial addition amount range of the mineral admixture according to the type of the mineral admixture, wherein:

[0118] The initial addition amount of the slag ranges from 20% to 70% of the mass of the sulphoaluminate clinker;

[0119] The initial addition amount of the fly ash ranges from 20% to 40% of the mass of the sulphoaluminate clinker;

[0120] The initial addition amount of the limestone powder is in the range of 0wt%-15wt%, and the initial addition amount of the silica fume is in the range of 5wt%-10wt%.

[0121] It should be noted that there may be multiple requirements for the preparation of the low-temperature grouting material of the present invention, that is, there may be multiple types of mineral admixtures selected.

[0122] This is because, according to different preparation requirements of low-temperature grouting materials, different types of mineral admixtures can be selected. When slag is added, the stability and strength of the low-temperature grouting material can be effectively improved, the shrinkage of the material during the hydration process can be prevented, and the amount of cementitious material used can be reduced. When fly ash is added, the strength of the low-temperature grouting material can be improved. When limestone powder is added, it can promote the early hydration of sulphoaluminate cement, and can also serve as a nucleation site for hydration products, promote the formation of the overall bearing structure, and increase the density of the slurry. However, the proportion of limestone powder participating in the reaction is relatively small, so the amount of addition should not be too much, and it is appropriate to be below 15wt%. When silica fume is added, due to the small particle size of silica fume, the specific surface area is large, and it has extremely strong surface activity. After mixing with cement materials, the volcanic ash effect and micro-aggregate effect occur, which can make the slurry structure more compact and can also reduce the amount of cementitious material used. When the initial addition amount of slag is in the range of 20% of the mass of sulphoaluminate clinker, the slag can be used as a cement material. %-70%, the initial addition amount of fly ash ranges from 20%-40% of the mass of the sulphoaluminate clinker, the initial addition amount of limestone powder ranges from 0wt%-15wt%, and the initial addition amount of silica fume ranges from 5wt%-10wt%, which can improve the physical and mechanical properties of the low-temperature grouting material; first, the initial addition amount range of the mineral admixture is determined by the type of selected mineral admixture to narrow the range of determining the optimal addition amount, and the optimal addition amount is found within the initial addition amount range, which can improve the efficiency of determining the optimal addition amount and facilitate the determination of the final optimal addition amount; then, several different addition amount values ​​are selected within the initial addition amount range to set up several groups of comparative tests, and the 1d compressive strength, 1d flexural strength and fluidity are detected and compared to see whether they are improved, and the optimal addition amount is obtained, so as to determine the type and optimal addition amount of the mineral admixture, so that the physical and mechanical properties of the prepared low-temperature grouting material are optimal and better suitable for low-temperature environments.

[0123] Optionally, the first physical property in step 3 includes initial fluidity, fluidity loss over time within one hour, and expansion rate;

[0124] The first mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength and 3d compressive strength;

[0125] The presence of an inhibitory effect means at least one of the following:

[0126] The basic grouting material has a 1d flexural strength under low temperature conditions that is less than 60% of the 1d flexural strength under normal temperature conditions, a 3d flexural strength under low temperature conditions that is less than 60% of the 3d flexural strength under normal temperature conditions, a 1d compressive strength under low temperature conditions that is less than 60% of the 1d compressive strength under normal temperature conditions, a 3d compressive strength under low temperature conditions that is less than 60% of the 3d compressive strength under normal temperature conditions, an initial fluidity under low temperature conditions that is less than 250mm, a fluidity loss over time within one hour under low temperature conditions that exceeds 20%, or a negative expansion rate under low temperature conditions.

[0127] Those skilled in the art can understand that by comparing the various performance factors of the basic grouting materials, such as initial fluidity, fluidity loss over one hour, expansion rate, 1d flexural strength, 3d flexural strength, 1d compressive strength and 3d compressive strength, under normal temperature and low temperature conditions, it can be objectively judged through data comparison whether the basic grouting materials can adapt well to the low temperature environment, and scientifically judged whether the low temperature conditions have an inhibitory effect on the basic grouting materials.

[0128] Optionally, the low temperature performance improvement in step 3 includes:

[0129] Step S1, increasing the dosage of at least one of the following types of ordinary Portland cement: ordinary Portland cement 32.5, ordinary Portland cement 42.5 or ordinary Portland cement 52.5;

[0130] or,

[0131] Step S2, adding an early strength admixture to the basic grouting material;

[0132] This is because, by increasing the dosage of at least one of the following types of ordinary Portland cement: ordinary Portland cement 32.5, ordinary Portland cement 42.5 or ordinary Portland cement 52.5, wherein the change ratio of the increased dosage of ordinary Portland cement is within 5wt%, the low-temperature grouting material suitable for low-temperature conditions can be obtained by appropriately adjusting the proportion of raw materials, and the change ratio is within 5wt%, which can prevent the component proportion from changing too much and thus changing the original performance of the material; by adding early strength admixtures to the basic grouting material, the low-temperature grouting material suitable for low-temperature conditions can be obtained by adjusting the type of raw materials, which not only ensures that the initial mix ratio remains unchanged, but also can conveniently and quickly improve the material properties.

[0133] Step S2 includes adding an early strength admixture to the basic grouting material according to the following steps:

[0134] Step S201, determining the dosage range of the early strength admixture, wherein the early strength admixture includes at least one of the following: sodium sulfate, aluminum sulfate, sodium nitrite, calcium nitrite, calcium nitrate, lithium carbonate, calcium formate, sodium gluconate, triethanolamine, triisopropanolamine, ethylene glycol, urea or sucrose, wherein the dosage range of the sodium sulfate is 0.3-3wt%, the dosage range of the aluminum sulfate is 0-4wt%, the dosage range of the sodium nitrite is 0.3-1wt%, the dosage range of the calcium nitrite is 0.3-1wt%, the dosage range of the nitric acid is 0. The dosage range of calcium is 0.5-5wt%, the dosage range of lithium carbonate is 0-0.1wt%, the dosage range of calcium formate is 0.1-2wt%, the dosage range of sodium gluconate is 0.03-0.07wt%, the dosage range of triethanolamine is 0.05-0.6wt%, the dosage range of triisopropanolamine is 0.2-0.9wt%, the dosage range of ethylene glycol is 3-5wt%, the dosage range of urea is 0-3wt%, and the dosage range of sucrose is greater than 0.2wt%;

[0135] This is because, the dosage range of the early strength admixture is first determined to quickly find the preferred early strength admixture within the dosage range, which can improve the efficiency of determining the preferred early strength admixture. Considering the actual needs and cost requirements, it is not advisable to add too much early strength admixture to avoid affecting the reaction of other components; then, X preferred early strength admixtures are determined by the dosage, and then the optimal dosage of the X preferred early strength admixtures is determined. Finally, the preferred early strength admixture is added to the basic grouting material according to the optimal dosage, and then the low-temperature performance of the basic grouting material is improved, so that the performance of the obtained low-temperature grouting material is optimal.

[0136] Step S202, determining X preferred early strength admixtures according to the dosage range, wherein X≥1;

[0137] Step S203, determining the optimal dosage of X preferred early strength admixtures;

[0138] Step S204, adding the preferred early strength admixture into the basic grouting material according to the optimal dosage;

[0139] In some possible embodiments, determining X preferred early-strength admixtures based on the dosage range includes: selecting 1-2 dosage values ​​within the dosage range of each of the early-strength admixtures, adding different early-strength admixtures to the basic grouting material according to the selected dosage values ​​to obtain several different first sample materials, testing and comparing the second mechanical properties and second physical properties of several first sample materials, and determining X preferred early-strength admixtures based on the second mechanical properties and the second physical properties; the second mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength, 3d compressive strength, cohesion and internal friction angle, and the second physical properties include initial fluidity, fluidity loss over time within one hour and expansion rate.

[0140] Among them, the second mechanical properties such as 1d flexural strength, 3d flexural strength, 1d compressive strength, 3d compressive strength, cohesion, internal friction angle are the main controlled quantities, and the second physical properties such as fluidity and expansion rate are the auxiliary controlled quantities. One or more suitable early strength admixtures are selected from several early strength admixtures. That is, the selected preferred early strength admixture needs to meet the following two points: a) one or more of the mechanical properties are improved, and the other mechanical properties cannot be reduced; b) the physical performance parameters are improved or reduced, and when reduced, the degree of reduction in fluidity loss over time within 1 hour cannot exceed 20%, and the expansion rate cannot be reduced to a negative value.

[0141] This is because, firstly, 1-2 dosage values ​​are selected within the dosage range of each of the early strength admixtures, and then a plurality of comparative experiments are designed, and different early strength admixtures are added to the basic grouting material according to the selected dosage values ​​to obtain a plurality of different first sample materials, and finally the second mechanical properties and the second physical properties of the plurality of first sample materials are tested and compared, and then X preferred early strength admixtures are selected according to the second mechanical properties and the second physical properties, so as to determine the optimal dosage of the subsequent preferred early strength admixtures.

[0142] The step S202 of determining X preferred early strength admixtures according to the dosage range includes:

[0143] Step S2021, selecting 1-2 dosage values ​​within the dosage range of each of the early strength admixtures,

[0144] Step S2022: adding different early strength admixtures to the basic grouting material according to the selected dosage values ​​to obtain a plurality of different first sample materials, and testing and comparing the second mechanical properties and the second physical properties of the plurality of first sample materials.

[0145] Step S2023, determining X preferred early strength admixtures according to the second mechanical properties and the second physical properties; the second mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength, 3d compressive strength, cohesion and internal friction angle; the second physical properties include initial fluidity, fluidity loss over time within one hour and expansion rate;

[0146] and:

[0147] When X=1, the determining of the optimal dosage of X preferred early strength admixtures includes: selecting N dosage point values ​​within the dosage range of the preferred early strength admixture, wherein N≥4, the N dosage point values ​​form an arithmetic progression, and the dosage point values ​​include two boundary values ​​of the dosage range; adding the preferred early strength admixtures with different dosage point values ​​to the basic grouting material according to the selected N dosage point values ​​to obtain N different second sample materials, testing and comparing the second mechanical properties and the second physical properties of the N second sample materials, and determining Y preferred dosages according to the second mechanical properties and the second physical properties, wherein Y≥1; when Y=1, the preferred dosage is the optimal dosage; when Y>1, performing X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy experiments on the Y second sample materials obtained under the Y preferred dosages, analyzing and comparing the phase composition and content of the Y second sample materials, and observing the morphology of the hydration products in the second sample materials, and then determining the optimal dosage from the Y preferred dosages;

[0148] When X>1, the determining of the optimal dosage of the X preferred early strength admixtures comprises: selecting N dosage point values ​​within the dosage range of each preferred early strength admixture, wherein N≥4, the N dosage point values ​​form an arithmetic progression, and the dosage point values ​​include two boundary values ​​of the dosage range; designing an orthogonal experiment, and adding different early strength admixtures with different dosage point values ​​to the basic grouting material according to the selected N dosage point values ​​to obtain (N) X Different second sample materials, tested and compared (N) X The second mechanical properties and the second physical properties of the second sample materials are determined, and Y preferred dosage combinations of X preferred early-strength admixtures are determined according to the second mechanical properties and the second physical properties, wherein Y ≥ 1; when Y = 1, the preferred dosage combination is the optimal dosage combination; when Y > 1, X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy experiments are performed on the Y second sample materials obtained under the Y preferred dosage combinations, the phase composition and content of the Y second sample materials are analyzed and compared, and the morphology of the hydration products in the second sample materials is observed, so as to determine the optimal dosage combination from the Y preferred dosage combinations.

[0149] Among them, the second mechanical properties such as 1d flexural strength, 3d flexural strength, 1d compressive strength, 3d compressive strength, cohesion, internal friction angle are the main controlled quantities, and the second physical properties such as fluidity and expansion rate are the auxiliary controlled quantities. The preferred dosage is selected from several dosages, that is, the selected preferred dosage needs to meet the following two points: a) one or more of the mechanical properties are improved, and the other mechanical properties cannot be reduced; b) the physical performance parameters are improved or reduced, and when reduced, the degree of reduction in fluidity loss over time within 1 hour cannot exceed 20%, and the expansion rate cannot be reduced to a negative value.

[0150] This is because, when only one preferred early-strength admixture is selected, firstly, N dosage point values ​​are selected within the dosage range, wherein N≥4, and the N dosage point values ​​form an arithmetic progression, and the dosage point values ​​include two boundary values ​​of the dosage range, so that the N dosage point values ​​are evenly distributed within the dosage range, and the selected N dosage point values ​​cover the dosage range interval, which is representative, so as to fully select the optimal dosage; then, according to the selected N dosage point values, the preferred early-strength admixture with different dosage point values ​​is added to the basic grouting material to obtain different second sample materials, with the second mechanical property as the main control quantity and the second physical property as the auxiliary The control amount is used to determine Y preferred dosages. If multiple preferred dosages meet the requirements at the same time, X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy experiments can be performed on the Y second sample materials obtained under the Y preferred dosages to analyze and compare the physical composition and content of the Y second sample materials, and the hydration product morphology is observed, and then the optimal dosage is determined from the Y preferred dosages; when multiple preferred early-strength admixtures are selected, an orthogonal experiment can be designed according to the above steps to select the best combination in the orthogonal experiment, and then the optimal dosage of the preferred early-strength admixture can be obtained, which can maximize the low-temperature improvement of the basic grouting material, so that the performance of the obtained low-temperature grouting material is optimal.

[0151] In order to further illustrate the technical solution of the present application in detail to support the technical problem to be solved by the present application, a specific example of the preparation method of the low-temperature grouting material is given below, such as Example 2.

[0152] Embodiment 2:

[0153] like Figure 3 As shown, this embodiment prepares the low-temperature grouting material through the following steps:

[0154] According to the early high strength properties of the low-temperature grouting material to be prepared, the type of sulphoaluminate cement required is determined to be early high strength sulphoaluminate cement, the sulphoaluminate cement comprises sulphoaluminate clinker and gypsum, and the water-cement ratio of the sulphoaluminate cement is 0.35;

[0155] The mass fraction W3 of anhydrous calcium sulphoaluminate in the sulphoaluminate cement is set to 30wt%;

[0156] According to the formula W1=W3 / W4, the mass fraction W1 of the sulphoaluminate clinker is determined to be 60wt%, wherein the mass fraction W4 of anhydrous calcium sulphoaluminate in the sulphoaluminate clinker is 50wt%;

[0157] According to the type of the sulphoaluminate cement, M=1 is determined, and according to M, the ratio C of the mass fraction W1 of the sulphoaluminate clinker to the mass fraction W2 of the gypsum is determined. G is 0.14, the C G Set to: Wherein, the mass fraction AC of anhydrous calcium sulfoaluminate in the sulfoaluminate clinker is 50wt%, and the mass fraction S of sulfur trioxide in the gypsum is 46wt%; according to the mass fraction W1 of the sulfoaluminate clinker and the mass fraction ratio C G Determine the mass fraction W2 of the gypsum to be 8wt%;

[0158] Determining the type of the gypsum as dihydrate gypsum according to the type of the sulphoaluminate cement;

[0159] The sulphoaluminate cement is prepared according to the mass fraction W1 of the sulphoaluminate clinker, the mass fraction W2 of the gypsum and the type of the gypsum;

[0160] Adding 7 wt % of ordinary Portland cement to the sulphoaluminate cement;

[0161] According to the preparation requirements of the low-temperature grouting material to improve the strength of the low-temperature grouting material, increase the density of the slurry and reduce the amount of cementitious material, the types of the mineral admixtures are selected as slag, limestone and silica fume;

[0162] Determine the initial addition amount range of the mineral admixture according to the type of the mineral admixture, wherein the initial addition amount range of the slag is 20%-70% of the mass of the sulphoaluminate clinker, the initial addition amount range of the limestone powder is 0wt%-15wt%, and the initial addition amount range of the silica fume is 5wt%-10wt%; select several different addition amount values ​​within the initial addition amount range of the same mineral admixture to set up several groups of comparative experiments, such as selecting the first group of comparative experiments to be 5wt% silica fume, 12wt% slag (20% of 60wt% of the mass of the sulphoaluminate clinker), and 8wt% limestone; the second group of comparative experiments to be 5wt% silica fume, 15wt% slag (60wt% of the mass of the sulphoaluminate clinker) The first comparative experiment was 25% of the mass of 60wt% of the sulphoaluminate clinker), 5wt% of limestone; the second comparative experiment was 5wt% of silica fume, 18wt% of slag (30% of the mass of 60wt% of the sulphoaluminate clinker), and 2wt% of limestone; the third comparative experiment was 5wt% of silica fume, 20wt% of slag (33% of the mass of 60wt% of the sulphoaluminate clinker), and 0wt% of limestone. The 1d compressive strength, 1d flexural strength, and fluidity of the sulphoaluminate cement before the addition of the mineral admixture and the sulphoaluminate cement after the addition of the mineral admixture in several comparative experiments were detected, and the addition amount of the mineral admixture in the comparative experiment when the 1d compressive strength, the 1d flexural strength, and the fluidity were the optimal values ​​was taken as the optimal value. The test results are as follows: the 1d flexural strength of the first group of comparative experiments is 5.99MPa, the 1d compressive strength is 45.42MPa and the initial fluidity is 249mm, the 1d flexural strength of the second group of comparative experiments is 6.78MPa, the 1d compressive strength is 46.23MPa, and the initial fluidity is 277mm, the 1d flexural strength of the third group of comparative experiments is 4.45MPa, the 1d compressive strength is 42.87MPa, and the initial fluidity is 267mm, the 1d flexural strength of the fourth group of comparative experiments is 4.17MPa, the 1d compressive strength is 51.17MPa, and the initial fluidity is 283mm; According to the above experimental results, due to the poor performance of the first group of comparative experiments in terms of fluidity and the initial fluidity It is about 250mm, which can meet the requirements, but the other groups have better flow properties under the condition of better strength, so the first group of comparative experiments is excluded; the third group of comparative experiments is excluded because of poor flexural strength and compressive strength; the fourth group of comparative experiments has excellent compressive strength and flow properties, but the flexural strength loss is large, so it is excluded; the final selection result is the second group of comparative experiments, which can maintain excellent flow properties, flexural and compressive strength. In summary, the optimal addition amount of slag is 15wt%, the optimal addition amount of limestone powder is 5wt%, and the optimal addition amount of silica fume is 5wt%; according to the type of the mineral admixture and the optimal addition amount, the mineral admixture is added to the sulphoaluminate cement to obtain a basic grouting material;

[0163] Testing the first mechanical properties and the first physical properties of the basic grouting material under normal temperature and low temperature conditions, respectively, to determine whether the low temperature condition has an inhibitory effect on the basic grouting material; the first physical properties include initial fluidity, fluidity loss over time within one hour, and expansion rate; the first mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength, and 3d compressive strength;

[0164] The test results show that the 1d flexural strength of the foundation grouting material under low temperature conditions loses 65%, which is less than 60% of the 1d flexural strength under normal temperature conditions, and the 1d compressive strength loses 73%, which is less than 60% of the 1d compressive strength under normal temperature conditions, indicating that there is an inhibitory effect;

[0165] Determine the dosage range of the early strength admixture, the early strength admixture includes: calcium formate, sodium sulfate and triethanolamine, wherein the dosage range of the sodium sulfate is 0.3-3wt%, the dosage range of the calcium formate is 0.1-2wt%, and the dosage range of the triethanolamine is 0.05-0.6wt%;

[0166] 1-2 dosage values ​​are selected within the dosage range of each early strength admixture, and different early strength admixtures are added to the basic grouting material according to the selected dosage values ​​to obtain several different first sample materials, and the second mechanical properties and second physical properties of several first sample materials are tested and compared. The test results show that calcium formate can improve 1d flexural strength and compressive strength when added, and the initial fluidity loss is within 20%, and the initial fluidity loss exceeds 20% when sodium sulfate is added. After triethanolamine is added, the fluidity is slightly improved, but the 1d flexural strength and compressive strength are not improved, and even the 3d flexural strength and compressive strength are reduced. According to the second mechanical properties and the second physical properties, it is determined that the preferred early strength admixture is calcium formate; the second mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength, 3d compressive strength, cohesion and internal friction angle, and the second physical properties include initial fluidity, fluidity loss over time within one hour, and expansion rate;

[0167] 10 dosage point values ​​are selected within the dosage range of the preferred early strength admixture, and the 10 dosage point values ​​form an arithmetic progression, and the dosage point values ​​include two boundary values ​​of the dosage range; according to the selected 10 dosage point values, the preferred early strength admixture with different dosage point values ​​is added to the basic grouting material to obtain 10 different second sample materials, and the second mechanical properties and the second physical properties of the 10 second sample materials are tested and compared, and the two preferred dosages of 0.3wt% and 0.5wt% are determined according to the second mechanical properties and the second physical properties, wherein when the preferred dosage is 0.3wt%, the 1d compressive strength is improved 59%, 3d compressive strength slightly improved, when the preferred dosage is 0.5wt%, 1d compressive strength increased by 79%, 3d compressive strength slightly decreased, the flexural strength of the preferred dosage of 0.5wt% is greater than the flexural strength of the preferred dosage of 0.3wt%, X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy experiments were performed on the two second sample materials obtained at the two preferred dosages, the phase composition and content of Y second sample materials were analyzed and compared, and the hydration product morphology in the second sample material was observed, and it was found that the microstructure and hydrate composition of the two were not much different, and then the optimal dosage was determined to be 0.5wt% from the two preferred dosages;

[0168] The preferred early-strength admixture is added to the base grouting material according to the optimal dosage, so that the low temperature condition has no inhibitory effect on the base grouting material, and the improved base grouting material is marked as the low-temperature grouting material to be prepared. The proportion of each component in the low-temperature grouting material is: 60wt% sulphoaluminate clinker, 8wt% gypsum, 7wt% ordinary Portland cement, 15wt% slag, 5wt% limestone powder, 5wt% silica fume and 0.5wt% calcium formate with the total mass of the above substances.

[0169] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a low-temperature grouting material, characterized in that: The steps include: Step 1: Select the type of sulphoaluminate cement according to the properties of the required low-temperature grouting material to prepare sulphoaluminate cement, wherein the sulphoaluminate cement is prepared by mixing sulphoaluminate clinker with a determined mass fraction and gypsum with a determined type and mass fraction; Step 2: Select a mineral admixture and add it to the prepared sulphoaluminate cement to obtain a basic grouting material; Step 3, testing the first mechanical property and the first physical property of the basic grouting material under normal temperature and low temperature conditions respectively; judging whether the low temperature condition has an inhibitory effect on the basic grouting material; and: If there is no inhibition, the basic grouting material is marked as the low-temperature grouting material to be prepared; If there is an inhibitory effect, the low-temperature performance of the basic grouting material is improved so that the low-temperature condition has no inhibitory effect on the basic grouting material, and the improved basic grouting material is marked as the low-temperature grouting material to be prepared.

2. The method for preparing the low-temperature grouting material according to claim 1, characterized in that: In the step 1, sulphoaluminate cement is selected according to the following principles; a. When the property of the low-temperature grouting material is early high strength, the type of sulphoaluminate cement selected is early high strength sulphoaluminate cement; b. When the property of the low-temperature grouting material to be prepared is expansion performance, the type of sulphoaluminate cement is selected as expansive sulphoaluminate cement; c. When the property of the low-temperature grouting material to be prepared is high self-stress, the type of sulphoaluminate cement selected is self-stress sulphoaluminate cement; d. When the property of the low-temperature grouting material to be prepared is low alkalinity, the type of sulphoaluminate cement selected is low-alkalinity sulphoaluminate cement.

3. The method for preparing the low-temperature grouting material according to claim 2, characterized in that: The step 1 includes the following sub-steps: Step 101, setting the mass fraction W3 of anhydrous calcium sulphoaluminate in the sulphoaluminate cement; Step 102, determining the mass fraction W1 of the sulphoaluminate clinker according to the mass fraction W3 of the anhydrous calcium sulphoaluminate; Step 103: Determine the type of gypsum and the mass fraction W2 of gypsum according to the type of sulphoaluminate cement and the mass fraction W1 of sulphoaluminate clinker.

4. The method for preparing the low-temperature grouting material according to claim 3, characterized in that: The mass fraction W3 of the anhydrous calcium sulphoaluminate is 30%-40%, and the water-cement ratio of the sulphoaluminate cement is 0.35-0.

5.

5. The method for preparing the low temperature grouting material according to claim 3, characterized in that , the operation of step 102 is as follows: according to the formula W1=W3 / W4, wherein W4 is the mass fraction of anhydrous calcium sulphoaluminate in the sulphoaluminate clinker.

6. The method for preparing the low-temperature grouting material according to claim 5, characterized in that: The step 103 comprises the following steps: Step 1031, determining M according to the type of the sulphoaluminate cement, wherein M is the ratio of the mass of sulfur trioxide in the gypsum to the mass of sulfur trioxide required for hydration of anhydrous calcium sulphoaluminate to form ettringite, and the value of M is determined according to the following principles; h. When the type of sulphoaluminate cement is early high-strength sulphoaluminate cement, M is 0-1; i. When the type of sulphoaluminate cement is expansive sulphoaluminate cement, M is 1-2; j. When the type of sulphoaluminate cement is self-stressed sulphoaluminate cement, M is 2-4; k. When the type of sulphoaluminate cement is low-alkalinity sulphoaluminate cement, M is 2.5-3. Step 1032: Determine the ratio C of the mass fraction W1 of the sulphoaluminate clinker to the mass fraction W2 of the gypsum according to the M. G , the C G Set to: Among them, A C is the mass fraction of anhydrous calcium sulphoaluminate in the sulphoaluminate clinker, which is the same as W4, and S is the mass fraction of sulfur trioxide in the gypsum; Step 1033: based on the mass fraction W1 of the sulphoaluminate clinker and the mass fraction ratio C G Determine the mass fraction W2 of the gypsum; Step 1034, determining the type of the gypsum according to the type of the sulphoaluminate cement is performed according to the following principles: w. When the property of the low-temperature grouting material is early high strength, when the type of the sulphoaluminate cement is early high strength sulphoaluminate cement, the type of the gypsum is dihydrate gypsum or anhydrous gypsum; x. When the property of the low-temperature grouting material to be prepared is expansion performance, when the type of the sulphoaluminate cement is expansive sulphoaluminate cement, the type of the gypsum is dihydrate gypsum; y. When the property of the low-temperature grouting material to be prepared is high self-stress, when the type of the sulphoaluminate cement is self-stress sulphoaluminate cement, the type of the gypsum is dihydrate gypsum; z. When the property of the low-temperature grouting material to be prepared is low alkalinity, when the type of the sulphoaluminate cement is low-alkalinity sulphoaluminate cement, the type of the gypsum is anhydrous gypsum. That is, based on principles a / b / c / d, the type of gypsum can also be directly determined based on the properties of the low-temperature grouting material.

7. The method for preparing the low-temperature grouting material according to claim 5, characterized in that: Before adding the mineral admixture to the prepared sulphoaluminate cement, the following steps are also included: 5-15wt% of ordinary Portland cement 32.5, 5-15wt% of ordinary Portland cement 42.5 or 5-15wt% of ordinary Portland cement 52.5 is added to the sulphoaluminate cement.

8. The method for preparing the low-temperature grouting material according to claim 5, characterized in that: The step 2 comprises: Step 201: According to the preparation requirements of the low-temperature grouting material, the type of the mineral admixture is selected, and the type of the mineral admixture includes at least one of the following: slag, fly ash, limestone powder or silica fume; wherein the type of the mineral admixture is selected according to the following principles: A. When the preparation requirement is to improve the strength of the low-temperature grouting material, the type of the mineral admixture is selected as slag or fly ash; B. When the preparation requirement is to increase the density of the slurry, the type of the mineral admixture is selected to be silica fume or limestone powder; C. When the preparation requirement is to reduce the amount of cementitious material, the type of the mineral admixture is selected as slag or silica fume; Step 202, determining the optimal amount of the mineral admixture according to the type of the mineral admixture comprises: Step 203: Determine the initial addition amount range of the mineral admixture according to the type of the mineral admixture, wherein: The initial addition amount of the slag ranges from 20% to 70% of the mass of the sulphoaluminate clinker; The initial addition amount of the fly ash ranges from 20% to 40% of the mass of the sulphoaluminate clinker; The initial addition amount of the limestone powder is in the range of 0wt%-15wt%, and the initial addition amount of the silica fume is in the range of 5wt%-10wt%.

9. The method for preparing the low-temperature grouting material according to claim 5, characterized in that: The first physical property in step 3 includes initial fluidity, fluidity loss over time within one hour, and expansion rate; The first mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength and 3d compressive strength; The presence of an inhibitory effect means at least one of the following: The basic grouting material has a 1d flexural strength under low temperature conditions that is less than 60% of the 1d flexural strength under normal temperature conditions, a 3d flexural strength under low temperature conditions that is less than 60% of the 3d flexural strength under normal temperature conditions, a 1d compressive strength under low temperature conditions that is less than 60% of the 1d compressive strength under normal temperature conditions, a 3d compressive strength under low temperature conditions that is less than 60% of the 3d compressive strength under normal temperature conditions, an initial fluidity under low temperature conditions that is less than 250mm, a fluidity loss over time within one hour under low temperature conditions that exceeds 20%, or a negative expansion rate under low temperature conditions.

10. The method for preparing the low-temperature grouting material according to claim 5, characterized in that: The low temperature performance improvement in step 3 includes: Step S1, increasing the dosage of at least one of the following types of ordinary Portland cement: ordinary Portland cement 32.5, ordinary Portland cement 42.5 or ordinary Portland cement 52.5; or, Step S2, adding an early strength admixture to the basic grouting material; Step S2 includes adding an early strength admixture to the basic grouting material according to the following steps: Step S201, determining the dosage range of the early strength admixture, wherein the early strength admixture includes at least one of the following: sodium sulfate, aluminum sulfate, sodium nitrite, calcium nitrite, calcium nitrate, lithium carbonate, calcium formate, sodium gluconate, triethanolamine, triisopropanolamine, ethylene glycol, urea or sucrose, wherein the dosage range of the sodium sulfate is 0.3-3wt%, the dosage range of the aluminum sulfate is 0-4wt%, the dosage range of the sodium nitrite is 0.3-1wt%, the dosage range of the calcium nitrite is 0.3-1wt%, the dosage range of the nitric acid is 0. The dosage range of calcium is 0.5-5wt%, the dosage range of lithium carbonate is 0-0.1wt%, the dosage range of calcium formate is 0.1-2wt%, the dosage range of sodium gluconate is 0.03-0.07wt%, the dosage range of triethanolamine is 0.05-0.6wt%, the dosage range of triisopropanolamine is 0.2-0.9wt%, the dosage range of ethylene glycol is 3-5wt%, the dosage range of urea is 0-3wt%, and the dosage range of sucrose is greater than 0.2wt%; Step S202, determining X preferred early strength admixtures according to the dosage range, wherein X≥1; Step S203, determining the optimal dosage of X preferred early strength admixtures; Step S204, adding the preferred early strength admixture into the basic grouting material according to the optimal dosage; The step S202 of determining X preferred early strength admixtures according to the dosage range includes: Step S2021, selecting 1-2 dosage values ​​within the dosage range of each of the early strength admixtures, Step S2022: adding different early strength admixtures to the basic grouting material according to the selected dosage values ​​to obtain a plurality of different first sample materials, and testing and comparing the second mechanical properties and the second physical properties of the plurality of first sample materials. Step S2023, determining X preferred early strength admixtures according to the second mechanical properties and the second physical properties; the second mechanical properties include 1d flexural strength, 3d flexural strength, 1d compressive strength, 3d compressive strength, cohesion and internal friction angle; the second physical properties include initial fluidity, fluidity loss over time within one hour and expansion rate; and: When X=1, the determining of the optimal dosage of X preferred early strength admixtures includes: selecting N dosage point values ​​within the dosage range of the preferred early strength admixture, wherein N≥4, the N dosage point values ​​form an arithmetic progression, and the dosage point values ​​include two boundary values ​​of the dosage range; adding the preferred early strength admixtures with different dosage point values ​​to the basic grouting material according to the selected N dosage point values ​​to obtain N different second sample materials, testing and comparing the second mechanical properties and the second physical properties of the N second sample materials, and determining Y preferred dosages according to the second mechanical properties and the second physical properties, wherein Y≥1; when Y=1, the preferred dosage is the optimal dosage; when Y>1, performing X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy experiments on the Y second sample materials obtained under the Y preferred dosages, analyzing and comparing the phase composition and content of the Y second sample materials, and observing the morphology of the hydration products in the second sample materials, and then determining the optimal dosage from the Y preferred dosages; Step S2023, when X>1, determining the optimal dosage of the X preferred early-strength admixtures comprises: selecting N dosage point values ​​within the dosage range of each preferred early-strength admixture, wherein N≥4, the N dosage point values ​​form an arithmetic progression, and the dosage point values ​​include two boundary values ​​of the dosage range; designing an orthogonal experiment, adding different early-strength admixtures with different dosage point values ​​to the basic grouting material according to the selected N dosage point values ​​to obtain (N) X Different second sample materials, tested and compared (N) X The second mechanical properties and the second physical properties of the second sample materials are determined, and Y preferred dosage combinations of X preferred early-strength admixtures are determined according to the second mechanical properties and the second physical properties, wherein Y ≥ 1; when Y = 1, the preferred dosage combination is the optimal dosage combination; when Y > 1, X-ray diffraction analysis, thermogravimetric analysis and scanning electron microscopy experiments are performed on the Y second sample materials obtained under the Y preferred dosage combinations, the phase composition and content of the Y second sample materials are analyzed and compared, and the morphology of the hydration products in the second sample materials is observed, so as to determine the optimal dosage combination from the Y preferred dosage combinations.

Citation Information

Patent Citations

  • A low-temperature post-tensioned prestressed duct grouting material

    CN102276218A

  • Sealing slurry for low-temperature environment as well as preparation method and application thereof

    CN111056800A

  • Low-temperature environment cement-based grouting material and preparation method thereof

    CN111116150A

  • Low-temperature early-strength tunnel lining filling material

    CN112694303A

  • Sleeve grouting material for low-temperature cement-based steel bar connection

    CN113880535A